2017
DOI: 10.1186/s12284-017-0173-2
|View full text |Cite
|
Sign up to set email alerts
|

Mesocotyl Elongation is Essential for Seedling Emergence Under Deep-Seeding Condition in Rice

Abstract: BackgroundDirect-seeding cultivation by deep-seeding of seeds (drill seeding) is becoming popular due to the scarcity of land and labor. However, poor emergence and inadequate seedling establishment can lead to yield loss in direct-seeding cultivation by deep-sowing. In rice, mesocotyl and coleoptile are primarily responsible for seedling emergence from deeper levels of soil.ResultsQuantitative trait loci (QTLs) for mesocotyl and coleoptile length at 5-cm seeding depth were detected using 98 backcross inbred l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 26 publications
1
39
0
Order By: Relevance
“…2 (Lee et al 2012b). Using the same population Lee et al (2017) found a QTL on chromosome 3 in both replication 1 (R 2 = 37.56%) and 2 (R 2 = 26.97%), and a QTL on chromosome 6 (R 2 = 8.28%) in replication 2 only.…”
Section: Phenotyping Methodsmentioning
confidence: 83%
See 2 more Smart Citations
“…2 (Lee et al 2012b). Using the same population Lee et al (2017) found a QTL on chromosome 3 in both replication 1 (R 2 = 37.56%) and 2 (R 2 = 26.97%), and a QTL on chromosome 6 (R 2 = 8.28%) in replication 2 only.…”
Section: Phenotyping Methodsmentioning
confidence: 83%
“…Generally, different emergence rate and mesocotyl length were observed among the varied sowing depths and mesocotyl length increased with the increase of sowing depth. In detail, the specific performance of mesocotyl length was 24.9 mm, 33.7 mm, and 36.5 mm at the sowing depth of 5 cm, 7 cm, and 10 cm, respectively (Lee et al 2017). Furthermore, the genotypes with long mesocotyl usually had stronger germination ability (Zhang et al 2005).…”
Section: Mesocotyl Elongation and Other Important Factors Affecting Dmentioning
confidence: 93%
See 1 more Smart Citation
“…Mesocotyl is a specialized organ located between the coleoptilar node and the basal part of the seminal root. Mesocotyl elongation is an important adaptive trait especially in the context of deep sowing tolerance or in the direct-seeding condition [17]. According to previous studies, this trait is regulated by the complex interaction of phytohormones [15,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Septiningsih et al (2013) used 118 simple sequence repeat (SSR) molecular markers and an F 2:3 population constructed from IR42 and Ma-Zhan Red to detect 6 QTLs related to seed germination and ooding tolerance under 10 cm ooding stress, and the BC 2 F 3 generation was used to verify the major effect locus qAG7.1 on chromosome 7 and estimate its contribution rate at 31.7%. Lee et al (2017) used backcross inbred lines (BILs) of Kasalath and Nipponbare to evaluate deep sowing (5 cm sowing depth) performance. With coleoptile length (CL) as an indicator, a QTL location assay identi ed sites that affected coleoptile elongation on chromosomes 3 and 5, and these sites explained phenotypic variations of 11.8% and 12.0%, respectively (Lee et al 2017).…”
mentioning
confidence: 99%